Study of Making Yogurt From Peanut (Arachis hypogaea L.) With The Addition of Coconut Water and Skim Milk - Lestari, Merinda (Proceedings of the International Conference on Green Technology; Vol 11 No 1 (2021): Proceeding of International Conference on Green Technology, 2021)
Abstract- Plant-based functional foods has been highly developed in recent years. Peanut ( Arachis hypogaea L.) can be used as functional drink that substitute for cow's milk. This study aimed to determine the effect of ratio (peanut milk and coconut water) and skim milk concentration on the quality of peanut yogurt. Yogurt was made by mixing peanut milk with coconut water and adding skim milk. The ratio of peanut milk and coconut water (50% : 50% and 75% : 25% v/v) and skim milk concentration (0%, 1% and 2% w/v). Fermentation was carried out at room temperature for 12 hours using commercial yogurt starter culture. Peanut yogurt analysis included of total LAB, pH, total acid and organoleptic. The data obtained were tabulated and presented descriptively. The best peanut yogurt was obtained in the ratio of peanut milk and coconut water (75%: 25%) and the addition of 2% skim milk which showed total LAB, pH and total acid were 9.2 x 10 9 CFU/mL, 2.8 and 0.37% respectively.